An investigation on the quality of midwifery services from the viewpoint of the clients in Isfahan through SERVQUAL model - Oliaee, Zohreh (Iran J Nurs Midwifery Res, 2016)
BACKGROUND: Quality of care is of great importance in health services as these services have the important mission to preserve health, and to give care to the society. The present study aimed to investigate the quality of midwifery services from the viewpoint of the clients, under coverage of health care centers in Isfahan, through SERVQUAL model. MATERIALS AND METHODS: This descriptive and analytical study was conducted on 218 subjects in 2014. Study population comprised the women referring to midwifery services clinics in health care centers in Isfahan. Data of the subjects (n = 218) were collected by SERVQUAL model containing the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. Data were analyzed by paired t-test, Spearman and Pearson correlation coefficients, and independent t-test through SPSS 20. RESULTS: There was a negative gap in all five relevant dimensions of giving services. The widest gap was in the mean of dimension of tangibles (−1.5), and the narrowest gap was in the dimension of assurance (−0.9). There was no significant association between the scores of expectations and perceptions, and age, education level, occupation, and marital status. CONCLUSIONS: The obtained negative gap showed that the level of service receivers' perception from existing condition was far from their expectation, and there was a wide gap between attaining their satisfaction with midwifery services and their expectation and reaching their appropriate level of services.